Studying the process of diesel fuel catalytic dewaxing using the unsteady mathematical model; Petroleum Science and Technology; Vol. 38, iss. 20 - Belinskaya N. S. Natalia Sergeevna; Frantsina E. V. Evgeniya Vladimirovna; Lutsenko A. S. Aleksey Sergeevich; Belozertseva N. E. Nataljya Evgenjevna; Ivanchina E. D. Emilia Dmitrievna (2020, 2020)
Title screen